KANDUNGAN Pb PADA TANAMAN PERKEBUNAN TEH DI SEKITAR RUAS JALAN - G. Gunawan (Purifikasi, 2003)
Abstract Result of air quality at road sides for Nox, SO2, O3, CO and SPM10, were still below ambient quality standard, with the average from morning till afternoon were NOx : 0,0127 ppm, SO2: 0,0251 ppm, O3 : 0,0535 ppm, CO: 0,0610 ppm, and SPM10: 54,4 ug/M3. The average hydrocarbon was more than air quality standard. The result of evaluation with ISPU on busy time where was classified as medium which was cause by the SPM10. Meanwhile, average lead (Pb) contain in tea leaf was 5,00 ppm in dry plant.